2014
DOI: 10.7869/tg.189
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral metabolism and bone mineral density in alcohol related and idiopathic chronic pancreatitis

Abstract: Background: There is limited information on the bone mineral metabolism in patients with chronic pancreatitis (CP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…Patients with chronic pancreatitis are at risk of osteoporosis and fracture because of numerous factors such as deteriorating pancreatic exocrine function, maldigestion and malabsorption of nutrients (especially fat-soluble vitamins and micronutrients), chronic systemic inflammation, abnormal bone turnover and, for some patients, ongoing alcohol excess and smoking [ 8 ]. We found low BMD in 53.4% (osteopenia 28.0% and osteoporosis 25.4%) of patients during a mean follow-up of 7.6 years after diagnosis of CP (897.6 person-years), which is lower compared to studies from Ireland [ 8 , 9 ], Germany [ 10 ], USA [ 11 ] and India [ 12 ], but higher than experiences from the Czech Republic [ 13 ] ( Table 4 ). A systematic review and meta-analysis that included 10 studies and 513 patients with CP showed a pooled prevalence rate for osteoporosis or osteopenia of 65% (23.4% prevalence for osteoporosis and 39.8% for osteopenia) [ 3 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Patients with chronic pancreatitis are at risk of osteoporosis and fracture because of numerous factors such as deteriorating pancreatic exocrine function, maldigestion and malabsorption of nutrients (especially fat-soluble vitamins and micronutrients), chronic systemic inflammation, abnormal bone turnover and, for some patients, ongoing alcohol excess and smoking [ 8 ]. We found low BMD in 53.4% (osteopenia 28.0% and osteoporosis 25.4%) of patients during a mean follow-up of 7.6 years after diagnosis of CP (897.6 person-years), which is lower compared to studies from Ireland [ 8 , 9 ], Germany [ 10 ], USA [ 11 ] and India [ 12 ], but higher than experiences from the Czech Republic [ 13 ] ( Table 4 ). A systematic review and meta-analysis that included 10 studies and 513 patients with CP showed a pooled prevalence rate for osteoporosis or osteopenia of 65% (23.4% prevalence for osteoporosis and 39.8% for osteopenia) [ 3 ].…”
Section: Discussioncontrasting
confidence: 56%
“…68,69 Given the high morbidity andmortality associated with fractures in older individuals and previous findings of osteopathy among CP patients, vitamin D supplementation is advisable. 30,49,70…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of comorbidities is illustrated by a study comparing patients having alcohol‐related pancreatitis to ones having idiopathic pancreatitis. As a group, patients with pancreatitis had low BMD, but no independent effect of alcohol abuse was noted (Prabhakaran et al., ). The inclusion of individuals with alcohol‐related secondary diseases may have contributed to variable results.…”
Section: Alcohol and Bonementioning
confidence: 99%